Effectiveness Project Based Learning in Teaching Speaking with Learner Motivation - Siti Munawaroh (Language-Edu, 2019)
This research was conducted to investigate whether there is any difference of students speaking skill who are taught project based learning and who are taught task based learning . there is any difference of students who have intrinsic motivation and students who have extrinsic motivation, and there is any interaction between PBL strategy and students’ motivationThe study was carried out in a population of 154 students of the XI grade at SMK NU Pace Nganjuk. A random sampling was done to select two classess out collection involved two of instruments, namely a speaking test and a questionnaire. The questionnaire in the form of topic familiarity assessment was administered to collect data of the learners’ motivation. The data from speaking test and questionnaire were used to predict students’ interest and student achievement on speaking skill . The data were analyzed by using ANOVA with the help of t SPSS v.20. the result turned out to confirm that there is significant positive effect project based learning on students’ speaking achievement and the interaction between students’ motivation and teaching technique.The result of the data analysis showed that the means of speaking of experimental group taught by using PBL strategy and the control group taught by task  based learning had statistically significant difference. It indicated that the students who were taught by using PBL strategy have better score in reading comprehension than those who are taught by using Task based Learning strategy.Then the analysis of interaction factor between learning method and learning motivation showed that there is interaction between PBL strategy and students’ motivation. It meant that PBL was more effective in intrinsic motivation than conventional strategy. Based on the previous result, the highes mean score was found in group of PBL strategy  with extrinsic motivation. While the lowest mean score was found in the task based learning with extrinsic motivation.Based on the result, the PBL strategy could be suggested to teacher as an alternative strategy for teaching speaking . but in this case, the students’ learning motivation influences how the students can speaking English well.Key words : speaking, PBL, motivation